Challenges of administrative data linkages: experiences of Administrative Data Research Centre for England (ADRC-E) researchers - Morris, Hannah; Lanati, Silvia; Gilbert, Ruth (International Journal of Population Data Science, 2018)
Background Linkage between administrative datasets routinely collected by government departments and other statutory bodies create rich resources for policy-relevant research. We describe how ADRC-E has achieved linkage between health and education data for England, and the challenges presented by this process. Methods A key task of ADRC-E is to progress exemplar studies of novel data linkages, and build relationships with data providers. While navigating untested data application and permission processes, ADRC-E researchers have maintained detailed timelines and developed a framework to improve the efficiency of future applications. Results The ADRC-E has approval to link four one-year birth cohorts of the National Pupil Database and Hospital Episode Statistics to facilitate research into outcomes for children with chronic conditions. The timeline of 3 years and 4 months represents 6 face-to-face meetings and 108 email and telephone correspondences. The technical challenges of data linkage have yet to be overcome before we receive data for research. Other examples of data timelines for cross-sectoral data linkage requests will be reported. Conclusions The shifting legal landscape governing the use of personal data, and a lack of precedent mean that unlocking administrative data for research requires substantial time, diligence and expertise on the part of both researcher and data provider.